Wartime relations intimacy, violence, and prostitution in occupied Poland, 1939-1945 - Röger, Maren 1981- (Oxford University Press, 2021)
During the Second World War, all contact between German soldiers and Polish women - considered an 'inferior race' - was officially banned. Sexual encounters frequently took place, however. Some were consensual, while others were characterised by brutal violence, and women often sold their bodies as a means of survival. The army and SS constructed purpose-built brothels for their soldiers, but also banned and frequently punished loving relationships. In Wartime Relations, Historian Maren Roeger gives a powerful account of these encounters and describes the actions of the army and the SS in regulating relations between soldiers and civilian women. Roeger provides new and important insights into everyday life during the occupation, Nazi racial policy, and the fates of the women involved
Keywords: Nationalsozialistische Deutsche Arbeiterpartei -- SS; Deutsches Reich -- Wehrmacht; Geschichte 1939-1945; Prostitution; Liebesbeziehung; Besetzung; Vergewaltigung; Polen